2007
DOI: 10.1038/nphys758
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical synapses causing self-organized criticality in neural networks

Abstract: Self-organized criticality 1 is one of the key concepts to describe the emergence of complexity in natural systems. The concept asserts that a system self-organizes into a critical state where system observables are distributed according to a power law. Prominent examples of self-organized critical dynamics include piling of granular media 2 , plate tectonics 3 and stick-slip motion 4 . Critical behaviour has been shown to bring about optimal computational capabilities 5 , optimal transmission 6 , storage of i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

23
637
4
7

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 531 publications
(671 citation statements)
references
References 18 publications
23
637
4
7
Order By: Relevance
“…The principles governing such adaptation at the macroscopic level of neuronal network dynamics are not well understood. Computational models and theory suggest that such adaptation can maintain critical network dynamics [14][15][16] , but these previous studies did not consider the strongly driven regime that is expected during intense sensory input. Indeed, sufficiently strong input may increase the overall excitability of a network by bringing neurons closer to their firing thresholds and potentially tipping the network into a high firing rate regime that is inconsistent with critical dynamics (Supplementary Information 1).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The principles governing such adaptation at the macroscopic level of neuronal network dynamics are not well understood. Computational models and theory suggest that such adaptation can maintain critical network dynamics [14][15][16] , but these previous studies did not consider the strongly driven regime that is expected during intense sensory input. Indeed, sufficiently strong input may increase the overall excitability of a network by bringing neurons closer to their firing thresholds and potentially tipping the network into a high firing rate regime that is inconsistent with critical dynamics (Supplementary Information 1).…”
mentioning
confidence: 99%
“…A subset of neurons (20%) was inhibitory. Motivated by previous experiments 21 and models 14 , we modelled adaptation as short-term synaptic depression with recovery (Methods). However, our model differed from previously studied models, as detailed in Supplementary Information 7.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This makes it difficult to perform a systematic study of the problem. Thus, it is necessary to investigate the typical cooperative phenomena in nonequilibrium systems.Recently, critical behaviors have been observed experimentally [1,2,3,4,5,6,7] and numerically [8,9,10,11,12,13,14,15] in typical examples of coupled excitable elements such as neural networks and cardiac tissues. In general, such critical behaviors are classified into several groups on the basis of the exponents of divergences.…”
mentioning
confidence: 99%
“…Typically, models of integrate-and-fire neurons on networks * Electronic address: jean-marc.luck@cea.fr † Electronic address: anita@bose.res.in have been studied, and their different dynamical regimes explored [21]. The discovery of neural avalanches in the brain [22] was followed by several dynamical models of neural networks [23,24], where the statistics of avalanches were investigated [25][26][27][28][29][30] in the context of theories of self-organised criticality [31]. A review of such approaches can be found in [32].…”
Section: Introductionmentioning
confidence: 99%